Análise da influência na tarifa e demanda da retirada dos cobradores dos ônibus do transporte público de Uberlândia (MG) - Furtado, Waldison França (2018)
Historically, the reduction of the public transport fare is a popular request, but it is due to the fact that in recent decades, fare adjustments have been disproportionate compared to the increase in the purchasing power of the population, contributing to the reduction of the number of displacements. At the same time, the demand of passengers has reduced in a way that compromises the efficiency and costing of the transit system. Some Brazilian cities aimed to reduce the cost of public transport and make the system more attractive to users, so they have adopted the withdrawal of bus ticket collectors as an alternative. However, this solution have not necessarily generate a positive impact on the user since there was no significant change to the price of the fare. In this sense, the main objective of this work is to measure the impact of the price of the fare by means of withdrawing the public transport collectors of Uberlandia - MG, subsidizing the public and private managers of the decision made about this change and its intent to predict the demand of passengers with the change of the amount charged from the user. For this, a new formulation based on the concepts of Geipot (1996) was used to determine the costs of the fare with and without collectors. It was concluded that keeping only the collectors in the stations, the tariff reduces from R $ 4.00 to R $ 3.65 and providing an increase in average monthly demand of 2.76%.